Step 1
Given; The system of equation;
![\begin{gathered} 5x-2y=-1--(a) \\ x-3y=5---(b) \\ \text{Required; To know if the point (-1,-2) is a solution to the system} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/amk60qlb0fqqco9xu3wq3s7cs25br3djlf.png)
Step 2
Input x=-1 and y=-2 in both equations and find if they will give -1 and 5 respectively.
![\begin{gathered} 5(-1)-2(-2)=-5+4=-1 \\ -1-3(-2)=-1+6=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/o7rgwkjz086ckah7es5ponii7qfpdndggm.png)
Since both equations gave us -1 and 5 respectively when we input x=-1 and y=-2, then we can conclude that the point (-1,-2) is a solution to the system.